Leader Member-Exchange and Job Involvement Impact on Innovative Work Behavior - M. Halid Sahaming; Tuty Sariwulan; Suherman; Hamidah (International Journal of Science and Society, 2022)
Innovation in the development of science and technology is important in increasing company’s competitiveness, especially in human resources. The study aimed at analysing leader-member exchange and job involvement on innovative work behavior. 205 employees of PT. Nindya Karya were collected for this study. The study results revealed that leader-member exchange in the company had positive impact on innovative work behavior, and employees’ job involvement had positive impact on innovative work behavior. Furthermore, interaction between leaders and employees and employees’ job involvement had significant impact on increasing innovative work behavior. It suggested that leaders should be able to encourage employees’ trust, and give concern for employees to encourage employees to contribute in achieving company goals as well as in improving job performance.